2021
DOI: 10.3389/fpsyt.2021.671007
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Alters Functional Gamma and Theta Resting-State Connectivity in Healthy Humans: Implications for Schizophrenia Treatment Targeting the Glutamate System

Abstract: Disturbed functional connectivity is assumed to cause neurocognitive deficits in patients suffering from schizophrenia. A Glutamate N-methyl-D-aspartate receptor (NMDAR) dysfunction has been suggested as a possible mechanism underlying altered connectivity in schizophrenia, especially in the gamma- and theta-frequency range. The present study aimed to investigate the effects of the NMDAR-antagonist ketamine on resting-state power, functional connectivity, and schizophrenia-like psychopathological changes in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 92 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…From a mechanistic perspective, we suggest N-Methyl-d-aspartate receptor (NMDAR) hypofunction to be involved in the oscillatory abnormalities and sensory processing deficits we identified in Nrxn1α −/− rats for two reasons. First, Nrxn1 has been shown to be important for postsynaptic NMDAR recruitment and function [ 3 , 25 ] and second, core endophenotypes found in our study, such as increased spontaneous gamma power and deficits in MMN-like responses can be induced by pharmacological blockade of NMDAR in rat [ 35 , 84 86 ], non-human primate [ 87 – 89 ] and human [ 90 92 ]. In this regard, our results line up with the NMDAR hypofunction hypothesis for SZ and ASD [ 93 , 94 ] by linking characteristic NMDAR-dependent translational endophenotypes to disease-relevant Nrxn1α deletions with construct validity.…”
Section: Discussionmentioning
confidence: 81%
“…From a mechanistic perspective, we suggest N-Methyl-d-aspartate receptor (NMDAR) hypofunction to be involved in the oscillatory abnormalities and sensory processing deficits we identified in Nrxn1α −/− rats for two reasons. First, Nrxn1 has been shown to be important for postsynaptic NMDAR recruitment and function [ 3 , 25 ] and second, core endophenotypes found in our study, such as increased spontaneous gamma power and deficits in MMN-like responses can be induced by pharmacological blockade of NMDAR in rat [ 35 , 84 86 ], non-human primate [ 87 – 89 ] and human [ 90 92 ]. In this regard, our results line up with the NMDAR hypofunction hypothesis for SZ and ASD [ 93 , 94 ] by linking characteristic NMDAR-dependent translational endophenotypes to disease-relevant Nrxn1α deletions with construct validity.…”
Section: Discussionmentioning
confidence: 81%
“…Although the reductions in theta power, theta frequency and firing rates that occurred were similar to those described in previous studies (Caixeta et al, 2013;Kittelberger et al, 2012;Kuang et al, 2010;Lazarewicz et al, 2010;Masuda et al, 2023), we did not observe any differences in gamma power, theta/gamma cross-coupling, or HFO power. This was surprising given that several previous studies have observed gamma range disruptions in humans (Curic et al, 2021;Hong et al, 2010) and animal models (Kittelberger et al, 2012;Lazarewicz et al, 2010), as well as disturbed theta/gamma cross-coupling under ketamine (Ahnaou et al, 2017;Caixeta et al, 2013;Michaels et al, 2018). Furthermore, NMDA receptor antagonists have also resulted in increased HFO power in both animal (Olszewski et al, 2013) and human (Nottage et al, 2023) studies.…”
Section: Discussionmentioning
confidence: 92%
“…A current source density analysis in one study showed increased gamma amplitude in the ventromedial prefrontal cortex, both the anterior and posterior cingulate cortex and the anterior insular (de la Salle et al 2016). In the other study, it was found that ketamine increased gamma connectivity in a network involving occipital, midline and frontal regions (Curic, Andreou et al 2021). We are not aware of any previous EEG or MEG human investigations of frequencies above 90 Hz with ketamine or of any studies of the gamma band or above with DCS.…”
Section: Resting State Spectral Amplitudesmentioning
confidence: 88%